2021 International Conference on Electronics, Communications and Information Technology (ICECIT) 2021
DOI: 10.1109/icecit54077.2021.9641131
|View full text |Cite
|
Sign up to set email alerts
|

Design and Development of a low cost Ultraviolet Disinfection system to reduce the cross infection of SARS-CoV-2 in ambulances

Abstract: In this study, a low-cost Ultraviolet disinfection system is proposed to be used inside ambulances for minimizing the cross-infection of Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) during patient transfer. The disinfection system consists of a tower unit that contains the Ultraviolet type C (UVC) light fixture and a control box where the power unit is placed. The UVC tower unit is portable, lightweight, and can be easily placed anywhere inside an ambulance. Two ultraviolet (UV) lamps used in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…These climatic elements can be incorporated into early warning systems to improve Dengue forecasting, vector management, and control in the future [ 53 ]. Vector control should follow according to the WHO’s Integrated Vector Management (IVM) system to regulate the vector’s breeding areas, lessen the vector’s environment management, decrease the stagnant areas of water, and maximize the use of larvicides, fogging, fumigation in camps, and the treatment of waste and wastewater before releasing into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…These climatic elements can be incorporated into early warning systems to improve Dengue forecasting, vector management, and control in the future [ 53 ]. Vector control should follow according to the WHO’s Integrated Vector Management (IVM) system to regulate the vector’s breeding areas, lessen the vector’s environment management, decrease the stagnant areas of water, and maximize the use of larvicides, fogging, fumigation in camps, and the treatment of waste and wastewater before releasing into the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental studies have shown that SARS-CoV-2 is highly active in conditions with low relative humidity and temperature, whereas genetic materials decay rapidly in an environment with high relative humidity and temperature [ 4 , 39 , 40 ]. When the virus is exposed to increased relative humidity, temperatures, and simulated solar light, the virus becomes even less stable (half-life, 3 min) [ 41 , 42 ]. In addition to the temperature factor, rainfall, and wind speed among other weather/meteorological factors influence the spread of COVID-19 [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Designing effective vaccines against SARS-CoV-2 variants is a very challenging issue as it is required to develop mutation-proof, variant-specific, and universal vaccines to prevent the spread of COVID-19 ( Gong et al, 2022 ; Park et al, 2022 ). In this regard, investigating SARS-COV-2 variants and unique mutations is essential for developing effective anti-COVID-19 drugs and vaccines ( Rakib et al, 2021 ; Jakariya et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%